Political Transformations, Endogenous Factors and Non-Political Actors (Studies of Transition States and Societies, 2013)
Starting with the current issue (Spring 2013), STSS will have a short editorial to present the articles and update the readers on the journal. The spring issue is extremely important for us (the editorial team), as it is the first one we are publishing after STSS has been admitted into SCOPUS. This has happened only 4 years after its creation and most credits go to Raivo Vetik, who came up with the idea of a journal (STSS) and served as editor-in-chief for the first three years.